Analysis on Food Security of Peatland Horticultural Farmer Households in Pontianak - Maswadi; Adi Suyatno; Muhammad Rizki (Agriecobis : Journal of Agricultural Socioeconomics and Business, 2023)
Food security, denoting the adequacy of food supply in terms of both quantity and quality for individuals within a given state, is a critical aspect of societal well-being. This research focuses on assessing the food security status of households engaged in peatland cultivation in Pontianak, West Kalimantan, Indonesia. The chosen research site, Siantan Hilir, was purposively selected due to its prominence as a hub for horticultural agricultural production within the sub-district. The study encompassed a population of 719 individuals, with a sample size of 42 respondents determined using the slovin formula. Primary data was procured through the observation and the administration of questionnaires to farmers, supplemented by secondary data. The findings unveiled a noteworthy trend where the household income of farmers exceeded their expenditures. However, a significant challenge emerged in the form of food expenditure constituting 64.86% of the total expenditures, thereby underscoring potential obstacles to maintaining food security. Furthermore, the moderate categorization of energy adequacy and the stark revelation that 88% of households lacked food security underscored the imperative for enhancements in managing food expenditures and refining consumption patterns in Siantan Hilir.